2019
DOI: 10.1212/wnl.0000000000006961
|View full text |Cite
|
Sign up to set email alerts
|

Education Research: An arts-based curriculum for neurology residents

Abstract: ObjectiveTo determine the feasibility and educational value of an arts-based curriculum for neurology residents, with the following specific learning objectives: to enhance communication and observational skills, increase awareness of point of view, and deepen appreciation of the narrative content of illness.MethodsNarrative medicine and visual thinking exercises, adopted from the study of literature and art history, were offered as monthly sessions in the neurology residents' conference schedule. Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…As a future direction, additional interventions, such as resilience skills training program [15], the arts-based curriculum for neurology residents [16], and increasing resident involvement in the design and development of the neurology clerkship rotation [17] can be implemented to improve residents teaching skills and medical student experience and education.…”
Section: Discussionmentioning
confidence: 99%
“…As a future direction, additional interventions, such as resilience skills training program [15], the arts-based curriculum for neurology residents [16], and increasing resident involvement in the design and development of the neurology clerkship rotation [17] can be implemented to improve residents teaching skills and medical student experience and education.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 12 studies reviewed, most studied outcomes of arts‐based interventions for medical students . Notably, most studies were non‐controlled cohort studies and used pre‐ or post‐intervention tests.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Only curricula designed and evaluated with the specific intent to enhance participants' observation skills were reviewed: 12 studies met these inclusion criteria ( Table 2).Of the 12 studies reviewed, most studied outcomes of arts-based interventions for medical students. 3,4,[6][7][8][9][10][11][12][13][14][15] Notably, most studies were non-controlled cohort studies and used pre-or post-intervention tests. Most evaluated arts-based curricula for medical students, and only three used a random control design.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with the previous studies, which showed an improved experience with the ambulatory rotation. 14 As a future direction, additional interventions, such as resilience skills training program 15 , the artsbased curriculum for neurology residents 16 , and increasing resident involvement in the design and development of the neurology clerkship rotation 17 can be implemented to improve residents teaching skills and medical student experience and education.…”
mentioning
confidence: 99%